Habitat fragmentation and logging affect the occurrence of lesser mouse-deer in tropical forest reserves - Muhammad Hazwan, .; Samantha, Liza D.; Tee, Sze Ling; Kamarudin, Norizah; Norhisham, Ahmad R.; Lechner, Alex M.; Azhar, Badrul (John Wiley & Sons, 2022)
Due to rapid urbanization, logging, and agricultural expansion, forest fragmentation is negatively affecting native wildlife populations throughout the tropics. This study examined the effects of landscape and habitat characteristics on the lesser mouse-deer, Tragulus kanchil, populations in Peninsular Malaysia. We conducted camera-trap survey at 315 sampling points located within 8 forest reserves. An assessment of site-level and landscape variables was conducted at each sampling point. Our study provides critical ecological information for managing and conserving understudied populations of T. kanchil. We found that the detection of T. kanchil was attributed to forest fragmentation in which forest patches had four times greater detection of T. kanchil than continuous forest. The detection of T. kanchil was nearly three times higher in peat swamp forest compared to lowland dipterocarp forests. Surprisingly, the detection of T. kanchil was higher in logged forests (logging ceased at least 30 years ago) than unlogged forests. The detection of T. kanchil increased with the presence of trees, particularly those with DBH of 5 cm to 45 cm, canopy cover, number of saplings and palms, number of dead fallen trees, and distance from nearest roads. However, detection decreased with a greater number of trees with DBH greater than 45 cm and higher elevations, and greater detections where creeping bamboo was abundant. We recommend that conservation stakeholders take the necessary steps (e.g., eradicating poaching, habitat degradation, and further deforestation) to support the conservation of mouse-deer species and its natural habitats.